Arthropod diversity associated with Bt and conventional cotton (Gossypium hirsutum L.) in Colombia - Pérez García, Karol (Revista Mexicana de Ciencias Agrícolas, 2017)
The use of genetically modified organisms (GMOs) has generated great expectations in the development of agro-crops. However, uncertainties arise about causal effects on the beneficial arthropofauna associated with the cotton crop. In this research the diversity of associated arthropofauna to the Bt cotton and conventional agroecosistema in the department of Córdoba-Colombia, in the cotton growing season 2013-2014, from October to March was evaluated. Arthropods were collected using five sampling methods according to the microhabitat; 23 787 individuals were collected, with a total of 240 taxa grouped into 25 species and 215 morphospecies; the most abundant order was Hemiptera and Coleoptera was the richer one. The diversity in both crops was similar with a richness of 0D= 240 for conventional and 0D= 233 for transgenic, alpha diversity for conventional was 1D= 36.39 and for Transgenic 1D= 33.39, regarding beta diversity in the two cultures it showed a value of 1,013 with q= 0, q= 1 and q= 2 of 1.001, results showed that the arthropods diversity for transgenic and conventional crops was not different and no significant differences between both cultures were shown.